The Influence of Service Quality, Ease of Application Use, and Price Perception on User Satisfaction of Netflix Application - Nida Nafisah Oktaviani; Beureukat Beureukat; Melati Melati; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the influence of Service Quality, Ease of Use of Applications, and Perceived Price on Satisfaction of Netflix Application Users. The research data used primary data through questionnaires on 100 respondents from FEB National University students Batch 2019. The data analysis technique used inferential analysis with multiple linear regression and used the help of the Statistical Product and Service Solution (SPSS) version 23 program. The results of multiple linear analysis shows that the variable Service Quality has a positive and significant effect on user satisfaction, Ease of Use Application has a positive and significant effect on user satisfaction, and Price Perception has a positive and significant effect on user satisfaction. The results of this study are expected to increase the attention of digital media streaming service providers, especially Netflix companies, regarding Service Quality, Application Ease of Use, and Price Perceptions which can increase sales.